Impact of the COVID-19 Pandemic on Receiving Dental Care Services From Community Health Centers in Iran - Roya Zamani; Reza Esmaeili; Elahe Moghimi Shahri; Ali Mohammad Mokhtari (Gonabad University of Medical Sciences, 2024)
Background: The fear of contracting coronavirus has influenced people's decisions regarding visiting crowded places, such as facilities providing medical and dental services. We aimed to investigate the impact of the COVID-19 pandemic on dental care utilization patterns in 16 community health centers in Gonabad.  Methods: This cross-sectional study utilized data from 16 community health centers in Gonabad from 2019 to 2021 (before and during the COVID-19 pandemic). Data pertaining to daily dental services, including check-ups, tooth extractions, tooth restorations, and scaling, were extracted and subsequently subjected to statistical analysis using SPSS software, version 22 at a significance level of <0.05. The independent-sample t-test was used to analyze normal variables and the Mann-Whitney test was used for other variables. Results: This study investigated information related to 11,850 dental services provided to 8,533 clients. The mean daily frequency of dental visits significantly decreased during the COVID-19 pandemic compared to the same period in the previous year (P<0.001). The ratio of tooth extractions to total daily dental visits increased from 0.45 to 0.64 during the pandemic, whereas the ratio of tooth restorations reduced from 0.33 to 0.03 in the same period (P<0.001).  Conclusion: The COVID-19 pandemic appears to have prompted individuals to postpone their visits to dental care centers and has also led to a shift in the demand for dental services demand from restorative procedures to more invasive treatments.